An Erwinia amylovora strain without plasmid pEA29 isolated in a nursery from hawthorn - Llop, Pablo; Donat, Victoria; López, María M.; Cabrefiga, Jordi; Ruz, Lidia; Montesinos, Emilio; Palomo, José L.; Rodriguez, Margarita (2017)
A strain of Erwinia amylovora (IVIA 1614-2a) was isolated in Segovia (central Spain) in 1996 from an outbreak of fire blight. E. amylovora was isolated from a Crataegus sp. which showed symptoms of the disease. The morphology of the colonies on several media (King’s B, SNA, CCT) was identical to that of reference strains. The strain was positive by ELISA using specific monoclonal antibodies, but not by PCR using primers designed from sequences of the plasmid pEA29. Nevertheless, the strain amplified with primers designed from chromosomic regions. The biochemical characterization using commercial strips API20E, API20NE, API50CH, and fatty acid profile gave the same results as the reference strain CFBP1430. On the other hand, strain IVIA 1614-2a resembled one E. amylovora strain cured from plasmid pEA29 in the slow growth in minimal medium without thiamine. The analyses of the plasmid content showed that it contains one plasmid of approx. 70 kb, with no homology with pEA29, reported as an ubiquitous plasmid present in pathogenic E. amylovora strains. This was demonstrated by comparing their restriction profiles using three enzymes and by hybridisation of the plasmid fragments obtained using the pEA29 as probe. Several virulence assays on pear and apple plants and fruits showed that this isolate had virulence levels similar to other pathogenic strains containing the pEA29 plasmid. As far as we know, this is the first report of the isolation from naturally infected plant material of a fully virulent strain of E. amylovora without plasmid pEA29.